Hindsiipropane B alleviates HIV-1 Tat-induced inflammatory responses by suppressing HDAC6-NADPH oxidase-ROS axis in astrocytes - Jo, Hyundong; Jang, Ha Young; Youn, Gi Soo; Kim, Donggyu; Lee, Chae Yeon; Jang, Jae Hee; Choi, Soo Young; Jun, Jong-Gab; Park, Jinseu (BMB reports, 2018)
Human immunodeficiency virus-1 (HIV-1) transactivator of transcription (Tat) is an important viral factor in neuroinflammation. Hindsiipropane B, present in Celastrus hindsii, possesses various biological mechanisms including antiinflammatory activity. In this report, we explored the regulatory activity of hindsiipropane B on HIV-1 Tat-mediated chemokine production and its mode of action in astrocytes. Hindsiipropane B significantly alleviated HIV-1 Tat-mediated production of inflammatory chemokines, CCL2, CXCL8, and CXCL10. Hindsiipropane B inhibited expression of HDAC6, which is important regulator in HIV-1 Tat-mediated chemokine production. Hindsiipropane B diminished HIV-1 Tat-mediated reactive oxygen species (ROS) generation and NADPH oxidase activation/expression. Furthermore, hindsiipropane B inhibited HIV-1 Tat-mediated signaling cascades including MAPK, NF-κB, and AP-1. These data suggest that hindsiipropane B exerts its inhibitory effects on HIV-1 Tat-mediated chemokine production via down-regulating the HDAC6-NADPH oxidase-MAPK-NF-κB/AP-1 signaling axis, and could serve as a therapeutic lead compound against HIV-1 Tat-associated neuroinflammation. [BMB Reports 2018; 51(8): 394-399].